Marketing Strategy as an Effort to Improve Competitiveness and Sales: A Case Study of Batik Malabis MSME in Bangkalan - Ilahi, Lailiy Kurnia; Suswanto, Budyi (Jurnal Intelek Insan Cendikia, 2025)
In today’s era of advanced globalization, competition in the business landscape is becoming increasingly intense, particularly within the fashion industry, including the batik sector. As a symbol of Indonesia’s rich cultural heritage, batik has evolved significantly, gaining popularity not only in domestic markets but also on an international scale. Once regarded solely as traditional attire, batik is now embraced as part of contemporary fashion that appeals to a wide range of consumers. Batik Malabis, a local batik business based in Bangkalan, Madura, is one of the enterprises that has actively adapted to these changing trends. By integrating traditional Madurese patterns with modern design elements, Batik Malabis seeks to engage a broader customer base—especially younger generations who are beginning to view batik not only as a cultural expression but also as a stylish and fashionable choice. This research adopts a qualitative method using a case study approach to explore the marketing strategies employed by Batik Malabis in boosting the sales of its modern batik products. This approach enables a thorough investigation into various aspects of marketing, including promotional tactics, pricing strategies, and the use of digital platforms tailored to the preferences and behaviors of the target market. Data were gathered through literature review from diverse sources such as scholarly journals, academic books, and industry publications related to marketing in the fashion and batik sectors. This provides a well-rounded understanding of the effectiveness of the marketing efforts implemented by the business. The purpose of this study is to examine how Batik Malabis applies marketing strategies to enhance product sales. Furthermore, the research aims to identify the strengths and weaknesses of these strategies, offering practical and relevant recommendations to support Batik Malabis in remaining competitive in a dynamic and increasingly challenging marketplace.